Seismic Performance Assessment of Regular and Irregular RC Buildings Under BNBC 2020 Using ETABS - Mahi, Md. Saniul Haque; Ridoy, Tanjun Ashravi; Hasan, Sakibul (Disaster in Civil Engineering and Architecture, 2025)
Seismic performance analysis is crucial to guaranteeing the structural safety of buildings, particularly in seismic-prone locations. This study examines the seismic performance of reinforced concrete (RC) structures with regular and irregular plan forms using ETABS v17 and the Equivalent Static Force Procedure (ESFP) based on the Bangladesh National Building Code (BNBC) 2020. This study focuses on the major earthquake characteristics such lateral displacement, story drift, base shear, torsional irregularity, and overturning moment. Seven alternative plan forms, including rectangle, square, T, U, W, H, and L-shaped structures, were examined to assess the impact of geometric imperfections on seismic response. The results demonstrate that irregular structures endure substantially greater lateral displacement and story drift than regular designs, particularly above the seventh story, which renders them more sensitive to seismic activity. The W-shaped structure maintained the largest base shear, but torsional irregularity was more noticeable in T, U, and H-shaped structures, showing their sensitivity to rotational impacts. Overturning moment study also suggested that irregular structures are more sensitive to instability induced by non-uniform distribution of pressures. All these discoveries underscore the requirement of optimal structural design, superior lateral load-resisting systems, and suitable reinforcing to limit seismic threats. The study emphasizes the need for compliance with seismic design codes and recommends that the incorporation of shear walls, bracing systems, and moment-resisting frames would be able to improve seismic strength. Future research should take into account sophisticated nonlinear dynamic analysis and retrofitting solutions to further increase the seismic resilience of irregular high-rise buildings.